Applications of Modified Starches 2018
DOI: 10.5772/intechopen.71626
|View full text |Cite
|
Sign up to set email alerts
|

Aspects on Starches Modified by Ionizing Radiation Processing

Abstract: Starch is one of the most studied natural polymers due to its widespread and applications as well as to the global interest regarding renewable, cheap, and easy to process resources. The native form of starch is frequently subjected to different processing methods in order to modify its structure and thus to obtain some functional properties suitable in specific industrial applications. Radiation-based method is a "green tool" for modification of natural polymers, such as starch, cellulose, pectin, and chitosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Previous studies determined the changes in digestibility during irradiation (Polesi et al, 2018). Based on the results in this study, there were many factors affected on EB irradiated starch: (i) the depolymerization of starch molecules (Pimpa et al, 2007), (ii) the formation of cross-linkages causing the increase of DRC (Brașoveanu and Nemțanu, 2018), and (iii) the breaking down of large crystals to smaller ones (Brasoveanu et al, 2013). The increase of RDS could be elevated by depolymerization resulting in the formation of smaller molecules that were easily attacked by digestive enzymes.…”
Section: In Vitro Digestibilitymentioning
confidence: 73%
See 2 more Smart Citations
“…Previous studies determined the changes in digestibility during irradiation (Polesi et al, 2018). Based on the results in this study, there were many factors affected on EB irradiated starch: (i) the depolymerization of starch molecules (Pimpa et al, 2007), (ii) the formation of cross-linkages causing the increase of DRC (Brașoveanu and Nemțanu, 2018), and (iii) the breaking down of large crystals to smaller ones (Brasoveanu et al, 2013). The increase of RDS could be elevated by depolymerization resulting in the formation of smaller molecules that were easily attacked by digestive enzymes.…”
Section: In Vitro Digestibilitymentioning
confidence: 73%
“…In contrast, the dose of >9 kGy caused a decrease in DRC. Researchers found that the formation of cross-linkages in starch molecules leading to this increase (Brașoveanu and Nemțanu, 2018). Other researchers reported dose up to 50 kGy did not affect on DRC.…”
Section: X-ray Diffraction Pattern and Relative Crystallinitymentioning
confidence: 96%
See 1 more Smart Citation
“…A possible explanation for these results consists of the appearance of free radicals at the interaction between accelerated electrons and plasticized starch, which were able to induce molecular changes and fragmentation in starch molecule. Thus, by glycosidic linkage decomposition, the number of macromolecules having small chains increased, and smaller starch granules were formed [ 12 , 13 , 14 , 17 ]. Additionally, due to electron beam irradiation, both C–C and C–O scissions occurred.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the free radicals produced by irradiation in composites may contribute to the oxidation of functional groups, and the oxidized macromolecules can suffer chain cleavage with decreases in molecular weight [ 11 ]. For example, the effect of an accelerated electron beam on starch consists of glycosidic bond decomposition, which further leads to macromolecule decomposition and the appearance of molecules with smaller chains [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%